Study on the Finite Element Simulation Method of the Belt Skew - Huang Zhuo; Han Fenglin; Yan Hongzhi; Li Peng (Jixie chuandong)
The belt skew caused by manufacturing and assembly tolerance frequently occurs in engineering practice. To research the characteristics of the belt skew,a finite element simulation method for the belt skew process based on ABAQUS is put forward. According to actual working conditions,focusing on the key technologies in the simulation,such as grid partition,the contact and friction models between the belt and the wheels,boundary conditions loading,and analysis of step division and setting. A specific post processing method which extracts the belt skew displacement in a fixed Eulerian coordinates is put forward. A belt skew experimental device is designed and the belt skew displacements are recorded when the steering wheel respectively had a deflecting angle of 0. 25° and 0. 5°. The simulation results are consistent with the experimental results,and the effectiveness of the proposed simulation method is proved.